Xibalbaonyx oviceps, a new megalonychid ground sloth (Folivora, Xenarthra) from the Late Pleistocene of the Yucatán Peninsula, Mexico, and its paleobiogeographic significance - Stinnesbeck, Sarah; Stinnesbeck, Wolfgang; Zell, Patrick; Hering, Fabio (Paläontologische Zeitschrift, 2017)
Here we describe a new genus and species of giant ground sloth, Xibalbaonyx oviceps (Megalonychidae, Xenarthra), from the drowned cave system of the northeastern Yucatán Peninsula. The specimen is Late Pleistocene in age and was discovered in the Zapote sinkhole (cenote) near Puerto Morelos in the Mexican state of Quintana Roo. Xibalbaonyx oviceps differs significantly from all hitherto known Megalonychidae including those from the Greater Antilles and South America. The new taxon suggests a local Caribbean radiation of ground sloths during the Late Pleistocene, which is consistent with the dispersal of the group along a Mexican corridor.
Gesehen am 22.02.2018